INVOLVEMENT OF CHILDREN WITH DISABILITIES INTO INCLUSIVE EDUCATION - Shokhsanam Abdurakhmanova (Web of Journals Publishing, 2024)
This article deals with the involvement of children with disabilities in inclusive education and its ways. The content, essence of inclusive education and the types of children with special educational needs who are involved in inclusive education are presented.
Keywords: inclusive education, Presidential Decree, children with special educational needs, their types, involvement in inclusive education.